On the activation of PhICl2 with pyridine. Issue 40 (21st April 2021) - Poynder, Tiffany B.; Chamorro Orué, Analia I.; Tania,; Sharp-Bucknall, Lachlan; Flynn, Matthew T.; Wilson, David J. D.; Athukorala Arachchige, Kasun S.; Clegg, Jack K.; Dutton, Jason L.
Abstract : PhICl2 reacts with pyridine to form a simple coordination complex via halogen bonding and does not result in an activated [PhI(Pyr)(Cl)] + cation as previously proposed. Abstract : It has been previously proposed that pyridines can activate PhICl2 by displacing a chloride and forming the [PhI(Pyr)(Cl)] + cation as a reactive intermediate. Here we show that pyridine does not displace chloride, but rather forms a weak complex with the iodine via halogen bonding along the C–I bond axis. This interaction is interrogated by NMR, structural, charge density, and theoretical investigations, which all indicate that pyridine does not activate PhICl2 as proposed.